Smooth muscle tumor of uncertain malignant potential (STUMP) - Yadav, Reena; Ansari, Sana; Chopra, Kanika; Agrawal, Kiran; Osama, Md Ali; Dhar, Swati (Nepal Journal of Obstetrics and Gynaecology, 2022)
Uterine smooth muscle tumor of uncertain malignant potential (STUMP) is a rare tumor belonging to a group of smooth muscle tumor that possess both benign and malignant features, complicating the diagnosis. STUMP is a rare uterine tumor with a paucity of literature available regarding management and subsequent malignant potential. A 22-year-old unmarried lady presented as uterine fibroids with 24 weeks size uterus. There was one intramural and another subserosal mass both of which revealed smooth muscle tumor of uncertain malignant potential in histopathology.